2019
DOI: 10.1007/s10072-019-03931-2
|View full text |Cite
|
Sign up to set email alerts
|

The inter-rater reliability of the Italian version of Aphasia Rapid Test (ART) for acute ischemic stroke

Abstract: Background The Aphasia Rapid Test (ART) is a screening questionnaire used for examining language in acute stroke patients. The ART was initially developed and validated in French. The purpose of this study was to assess the inter-rater reliability of the Italian ART. Methods The original version of the ART was translated into Italian. The inter-rater reliability was assessed by two independent neurologists who were blind to each other's ratings in 52 acute post-stroke patients. Results The 52 patients (28 men,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
(6 reference statements)
3
3
0
Order By: Relevance
“…Secondly, on day eight, the authors measured the interrater reliability of the test, yielding a good concordance correlation coefficient of 0.959. This finding is in line with the French study of Azuar et al with a coefficient of concordance of 0.990 (rater 1=13.4, rater 2=13.49) [11], and the Italian study of Panebianco et al with a coefficient of concordance of 0.99 (rater 1=9.38, rater 2=9) [13]. Also, the Portuguese study of Tábuas-Pereira et al reported an excellent concordance coefficient (0.985) between rater 1 and rater 2 [14].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Secondly, on day eight, the authors measured the interrater reliability of the test, yielding a good concordance correlation coefficient of 0.959. This finding is in line with the French study of Azuar et al with a coefficient of concordance of 0.990 (rater 1=13.4, rater 2=13.49) [11], and the Italian study of Panebianco et al with a coefficient of concordance of 0.99 (rater 1=9.38, rater 2=9) [13]. Also, the Portuguese study of Tábuas-Pereira et al reported an excellent concordance coefficient (0.985) between rater 1 and rater 2 [14].…”
Section: Discussionsupporting
confidence: 90%
“…The authors found a mean of 173 seconds for the administration of ART. This duration is close to findings from Italian, French, and Portuguese studies that reported the mean duration of 169, 171, and 154 seconds, respectively [11,13,14]. Thus, the present study indicates that similar to other versions the Persian version of ART can be completed in a short time, making it a suitable tool for aphasia measurement at the bedside.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations